2019
DOI: 10.30862/jhm.v2i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Penggunaan LKM Berbasis Hots (Higher Order Thinking Skills) Terhadap Hasil Belajar Mahasiswa Pendidikan Matematika

Abstract: The purpose of this study was to determine the effectiveness of the use of student activity sheet (SAS) based on Higher Level Thinking Skills (HOTS) on learning outcomes of mathematics student. This research is a quantitative, quasi-experimental method using the nonequivalent control group research design. Data collection uses documentation and tests to measure learning outcomes. The data obtained were analyzed statistically using descriptive analysis and inferential analysis. Descriptive analysis includes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…The concept used to work on the problem is the friction force concept only, which can be developed by integrating it into the braking force. Implementing one concept into two concepts will increase the complexity of the problem (Nurmala & Mucti, 2019;Sagala & Andriani, 2019). Next, the point of non-algorithmic where the question has only one direct answer, that is, the tire will be quickly slipping.…”
Section: Figure 1 Recapitulation Of Rater's Assessment Results On Conformity Aspect With the Characteristics Of Hots Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept used to work on the problem is the friction force concept only, which can be developed by integrating it into the braking force. Implementing one concept into two concepts will increase the complexity of the problem (Nurmala & Mucti, 2019;Sagala & Andriani, 2019). Next, the point of non-algorithmic where the question has only one direct answer, that is, the tire will be quickly slipping.…”
Section: Figure 1 Recapitulation Of Rater's Assessment Results On Conformity Aspect With the Characteristics Of Hots Questionsmentioning
confidence: 99%
“…The learning process that uses HOTS as the basis in the process can increase the learning process's meaning because students memorize the materials taught, understand, analyze, and implement their knowledge to solve problems (Hassan, Rosli, & Zakaria, 2016). HOTS is a higher way of thinking than memorizing facts, presenting facts, or applying rules, formulas, and procedures (Andoko, 2020;Nurmala & Mucti, 2019). HOTS skills are when he is already in the top three levels in the revised Bloom's Taxonomy, namely at the analysis, evaluation, and creation stage (Fadzam & Rokhimawan, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research findings also stated that HOTS can improve students' critical thinking skills (Hamdi et al, 2018;Pratama & Retnawati, 2018). Other research findings also state that using Hots-Based worksheets (Higher Order Thinking Skills) can improve student learning outcomes (Khotimah & Sari, 2020;Nurmala & Mucti, 2019). It can be concluded that HOTS can help students improve critical thinking skills.…”
Section: Introductionmentioning
confidence: 92%
“…HOTs include skills to analyze (analyzing), evaluate (evaluating), create (creating), critical thinking (critical thinking), and problem-solving (problem-solving) (Johanns et al, 2017;Retnawat et al, 2018;Zulfiani et al, 2020). One of these skills in creating and developing HOTS-based learning tools according to 21st-century life (Nurmala & Mucti, 2019). Besides, the teacher must have the skills to encourage students to think critically or think at a higher level.…”
Section: Introductionmentioning
confidence: 99%